Pentingnya Critical Thinking dalam Menghadapi Tantangan Dunia Kerja dan Kehidupan Sehari-Hari - Diana Zumrotus Sa’adah; Desty Arnita; Heli Pera Mistika; Heru Kurnia Sesba; Mallfi Lutfia (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Critical thinking is an essential skill in the modern era, characterized by rapid changes in the workplace and the dynamics of daily life. In a time when information is readily accessible and challenges are increasingly complex, individuals are required not only to master technical skills (hard skills), but also to possess the ability to analyze, evaluate, and critically respond to information. These skills are the foundation for making informed, wise, and adaptive decisions. Case studies from various recent news outlets in Indonesia show that many young people, especially Gen Z, still face difficulties entering the workforce due to a lack of soft skills and mental preparedness. This phenomenon is evident in increasing reports of unpreparedness for work pressure, poor communication skills, and a lack of problem-solving skills. Through an analysis of the literature and news reports, this article explores the relationship between critical thinking skills and the real-world challenges faced by Gen Z. Furthermore, it offers practical recommendations for developing critical thinking capacity so that young people can better adapt, improve professional performance, and respond to various issues in daily life more maturely and responsibly.